Surveillance of tick-borne bacteria infection in ticks and forestry populations in Inner Mongolia, China - Duan, Like; Zhang, Lin; Hou, Xuexia; Bao, Zihao; Zeng, Yu; He, Lijuan; Liu, Zeliang; Zhou, Haijian; Hao, Qin; Dong, Aiying (Frontiers in Public Health, 2024)
Ticks are one of the most important vectors that can transmit pathogens to animals and human beings. This study investigated the dominant tick-borne bacteria carried by ticks and tick-borne infections in forestry populations in Arxan, Inner Mongolia, China. Ticks were collected by flagging from May 2020 to May 2021, and blood samples were collected from individuals at high risk of acquiring tick-borne diseases from March 2022 to August 2023. The pooled DNA samples of ticks were analyzed to reveal the presence of tick-borne bacteria using high-throughput sequencing of the 16S rDNA V3–V4 region, and species-specific polymerase chain reaction (PCR) related to sequencing was performed to confirm the presence of pathogenic bacteria in individual ticks and human blood samples. All sera samples were examined for anti-SFGR using ELISA and anti-B. burgdorferi using IFA and WB. A total of 295 ticks (282 Ixodes persulcatus and 13 Dermacentor silvarum) and 245 human blood samples were collected. Rickettsia, Anaplasma, Borrelia miyamotoi, and Coxiella endosymbiont were identified in I. persulcatus by high-throughput sequencing, while Candidatus R. tarasevichiae (89.00%, 89/100), B. garinii (17.00%, 17/100), B. afzelii (7.00%, 7/100), and B. miyamotoi (7.00%, 7/100) were detected in I. persulcatus, as well the dual co-infection with Candidatus R. tarasevichiae and B. garinii were detected in 13.00% (13/100) of I. persulcatus. Of the 245 individuals, B. garinii (4.90%, 12/245), R. slovaca (0.82%, 2/245), and C. burnetii (0.41%, 1/245) were detected by PCR, and the sequences of the target genes of B. garinii detected in humans were identical to those detected in I. persulcatus. The seroprevalence of anti-SFGR and anti-B. burgdorferi was 5.71% and 13.47%, respectively. This study demonstrated that Candidatus R. tarasevichiae and B. garinii were the dominant tick-borne bacteria in I. persulcatus from Arxan, and that dual co-infection with Candidatus R. tarasevichiae and B. garinii was frequent. This is the first time that B. miyamotoi has been identified in ticks from Arxan and R. solvaca has been detected in humans from Inner Mongolia. More importantly, this study demonstrated the transmission of B. garinii from ticks to humans in Arxan, suggesting that long-term monitoring of tick-borne pathogens in ticks and humans is important for the prevention and control of tick-borne diseases.